Glucosamine protects against neuronal but not vascular damage in experimental diabetic retinopathy - Rachana Eshwaran; Matthias Kolibabka; Gernot Poschet; Gregor Jainta; Di Zhao; Loic Teuma; Katharina Murillo; Hans-Peter Hammes; Martina Schmidt; Thomas Wieland; Yuxi Feng (Elsevier, 2021)
Objective: Glucosamine, an intermetabolite of the hexosamine biosynthesis pathway (HBP), is a widely used nutritional supplement in osteoarthritis patients, a subset of whom also suffer from diabetes. HBP is activated in diabetic retinopathy (DR). The aim of this study is to investigate the yet unclear effects of glucosamine on DR. Methods: In this study, we tested the effect of glucosamine on vascular and neuronal pathology in a mouse model of streptozotocin-induced DR in vivo and on cultured endothelial and Müller cells to elucidate the underlying mechanisms of action in vitro. Results: Glucosamine did not alter the blood glucose or HbA1c levels in the animals, but induced body weight gain in the non-diabetic animals. Interestingly, the impaired neuronal function in diabetic animals could be prevented by glucosamine treatment. Correspondingly, the activation of Müller cells was prevented in the retina as well as in cell culture. Conversely, glucosamine administration in the normal retina damaged the retinal vasculature by increasing pericyte loss and acellular capillary formation, likely by interfering with endothelial survival signals as seen in vitro in cultured endothelial cells. Nevertheless, under diabetic conditions, no further increase in the detrimental effects were observed. Conclusions: In conclusion, the effects of glucosamine supplementation in the retina appear to be a double-edged sword: neuronal protection in the diabetic retina and vascular damage in the normal retina. Thus, glucosamine supplementation in osteoarthritis patients with or without diabetes should be taken with care.